Pengaruh Harga Iklan dan Kemasan Berita Terhadap Persepsi Positif Pengiklan Dalam Program Berita di PT Lativi Media Karya (tvOne) - Heru Sudinta; heru sudinta (Esensi Daruna : Jurnal Komunikasi, 2025)
The transition from analog to digital broadcasting has made competition for advertising increasingly competitive. Even Television Commercials (TVCs) now have to compete with the local television market, which is cheaper than national television. The study was conducted at the television station tvOne by analyzing the influence of advertising prices and news packaging on the positive perception of advertisers in news programs. This study uses a quantitative research method with 3 variables, namely 2 independent variables (advertising prices and news packaging), and a dependent variable (Advertiser Perception). The population of this study was 120 advertisers, Marketing Agencies, Political Figures, Regional Heads, Lecturers, and Entrepreneurs who had advertised in news programs during 2023-2024. Data analysis was carried out using SPSS software version 13.00. The results showed that the Advertising Price variable influenced Advertiser Positive Perception with a coefficient of determination of 3.9%. News packaging also influenced Advertiser Positive Perception with a coefficient of determination of 13.9%. Together, the Advertising Price and news packaging variables also have an influence on the Advertiser's Positive Perception variable, with a combined determination coefficient of 14.1%. Conclusion that Advertising Price and news packaging together are able to explain 0.141 or equal to 14.1% of the variation in Advertiser's Positive Perception, while the remaining 0.839 or equal to 83.9% is explained by other factors not included in this study. This proves that the Advertising Price and news packaging variables have an influence on Advertiser's Positive Perception of News Programs at tvOne. Peralihan siaran analog ke digital membuat persaingan dalam memperoleh iklan juga semakin kompetitif. Bahkan Television Commercial (TVC) kini harus bersaing dengan pasar televisi lokal yang harganya lebih murah daripada televisi nasional. Penelitian dilakukan di stasiun televisi PT. Lativi Media Karya (tvOne) dengan menganalisa pengaruh harga iklan dan kemasan pemberitaan terhadap persepsi positif pemasang iklan di program acara berita. Penelitian ini menggunakan metode penelitian kuantitatif dengan 3 variabel, yaitu 2 variabel bebas/independen (harga iklan dan kemasan pemberitaan), dan variabel terikat/dependen (Persepsi Pemasang Iklan). Populasi penelitian ini adalah 120 pemasang iklan, Marketing Agency, Tokoh Politik, Kepala Daerah, Dosen, dan Pengusaha yang pernah memasang iklan di program berita selama tahun 2023-2024. Analisis data dilakukan dengan menggunakan software SPSS versi 13.00. Hasil penelitian menunjukkan bahwa variabel Harga Iklan berpengaruh terhadap Persepsi Positif Pemasang Iklan dengan koefisien determinasi sebesar 3,9%. Kemasan pemberitaan juga berpengaruh terhadap Persepsi Positif Pemasang Iklan dengan koefisien determinasi sebesar 13,9%. Secara bersama-sama, variabel Harga Iklan dan kemasan pemberitaan juga memiliki pengaruh terhadap variabel Persepsi Positif Pemasang Iklan, dengan koefisien determinasi gabungan sebesar 14,1%. Dapat disimpulkan bahwa Harga Iklan dan kemasan pemberitaan secara bersama-sama mampu menjelaskan 0,141 atau sama dengan 14,1% variasi dalam Persepsi Positif Pemasang Iklan, sementara sisanya 0,839 atau sama dengan 83,9%% dijelaskan oleh factor-faktor lain yang tidak termasuk dalam penelitian ini. Hal in membuktikan bahwa variabel Harga Iklan dan kemasan pemberitaan mempunyai pengaruh terhadap Persepsi Positif Pemasang Iklan Program Berita di PT. Lativi Media Karya (tvOne)